ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINER DUA VARIABEL - Afifah, Laili Nur; Rif'at, Mohamad; Hartoyo, Agung (UNIVERSITAS TANJUNGPURA, 2023)
The goal of this study was to find out how well SMP Negeri 2 Sungai Ambawang students solved two-variable linear equation systems using creative thinking. Case studies are used as the descriptive research method. The research subjects were 6 students with details of 2 having high mathematical abilities, 2 having moderate mathematical abilities, and 2 having low mathematical abilities taken from the average daily test score. Data collection techniques used are tests and interviews. In this study, there were 2 students who met the indicators of fluency, flexibility and novelty, 2 students met the indicators of fluency and flexibility, 2 students met the indicators of fluency. In general, it can be concluded that the students' creative thinking ability in solving the problems of a two-variable system of linear equations in students of SMP Negeri 2 Sungai Ambawang is a student with high mathematical ability, creative thinking ability meets the indicators of fluency, flexibility, and novelty. students who have moderate mathematical ability seem to have not met the novelty indicator. students with low math ability seem to still not be able to meet the flexibility and novelty indicators.Keyword: Creative Thinking Ability, Two-Variable System Of Linear Equations